Asymptotic Behaviour of a Viscoelastic Transmission Problem with a Tip Load - Rivera, J. E. M.; Carneiro, M. S.; Fernandes, M. A. A. (Trends in Computational and Applied Mathematics, 2023)
We consider a transmission problem for a string composed by two components: one of them is a viscoelastic material (with viscoelasticity of memory type), and the other is an elastic material (without dissipation effective over this component). Additionally, we consider that in one end is attached a tip load. The main result is that the model is exponentially stable if and only if the memory effect is effective over the string. When there is no memory effect, then there is a lack of exponential stability, but the tip load produces a polynomial rate of decay. That is, the tip load is not strong enough to stabilize exponentially the system, but produces a polynomial rate of decay.